ANALISA PENGENDALIAN INTERNAL TERHADAP PELAYANAN DI TERMINAL BANDAR UDARA ALKHA - Andi Martias (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2018)
Revitalizing the vision of the company is a continuous planning that the company anticipates all the changes around it. Some of the internal controls carried out by management have not been able to eliminate or reduce the problems that arise in the management of Terminal Services. This research is an event study that is looking at the process of internal control over airport terminal service management process. Based on the results of field observations note that: 1) Some Airline still oriented to put forward the convenience factor of work and less understanding of the needs of its customers 2) Large investment cost without followed by efforts to increase Customer Service Knowledge and Skill adequate for employees, 3) in the field has not been decomposed in detail, 4) an information collected derived from various sources, managed partially (unintegrated), 4) Risk Profile is not up to date / update, no longer relevant in mitigating risks and internal control reference for airport management, 5) Reward and punishment for the achievement of KPI can not be applied comprehensively. This increase of control starts from the top management level to the operators in the field, either from policy, procedure, knowledge and skill or quantity in harmony with their respective competence. Keywords: Historical Experience,Internal Control .